Технологии изготовления фотонных кристаллов - Berezianskyi, B. M. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
A review of methods for fabricating photonic crystals for nanophotonic integrated circuits is presented. A comparative analysis of existing technologies has been carried out. The prospects of applying these technologies under industrial production conditions of devices based on photonic crystals are considered. Conclusions are drawn regarding the use of methods in various industrial environments.